2017
DOI: 10.1155/2017/7874251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Montmorillonite on the Mineralization and Cementing Properties of Microbiologically Induced Calcium Carbonate

Abstract: Carbonate mineralization microbe is a microorganism capable of decomposing the substrate in the metabolic process to produce the carbonate, which then forms calcium carbonate with calcium ions. By taking advantage of this process, contaminative uranium tailings can transform to solid cement, where calcium carbonate plays the role of a binder. In this paper, we have studied the morphology of mineralized crystals by controlling the mineralization time and adding different concentrations of montmorillonite (MMT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Figure 1a shows a representative scanning electron microscopy (SEM) image of SrCO 3 particles which have a slightly spherical shape, obtained after a mineralization time of 6 h. Figure 1b shows dumbbell-like SrCO 3 obtained after a mineralization time of 12 h. Interestingly, with the increase of the mineralization time, the dumbbell-like SrCO 3 turned into popcorn-like SrCO 3 via the process of dissolution and recrystallization, see Figure 1c. By magnifying Figure 1c, we can clearly see that there are many voids left by the death of the bacteria on the surface of the SrCO 3 crystal, indicating that the microorganism acts as a nucleation site for SrCO 3 crystallization, which is consistent with the experimental results of Chen et al [24,25,26]. The change in the surface morphology could reflect the dissolution and recrystallization process of nano-spherical SrCO 3 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure 1a shows a representative scanning electron microscopy (SEM) image of SrCO 3 particles which have a slightly spherical shape, obtained after a mineralization time of 6 h. Figure 1b shows dumbbell-like SrCO 3 obtained after a mineralization time of 12 h. Interestingly, with the increase of the mineralization time, the dumbbell-like SrCO 3 turned into popcorn-like SrCO 3 via the process of dissolution and recrystallization, see Figure 1c. By magnifying Figure 1c, we can clearly see that there are many voids left by the death of the bacteria on the surface of the SrCO 3 crystal, indicating that the microorganism acts as a nucleation site for SrCO 3 crystallization, which is consistent with the experimental results of Chen et al [24,25,26]. The change in the surface morphology could reflect the dissolution and recrystallization process of nano-spherical SrCO 3 .…”
Section: Resultssupporting
confidence: 87%
“…The spherical SrCO 3 crystals gradually aggregated together via dissolution and recrystallization under the action of microbial secretion to form popcorn-like SrCO 3 crystals. Because of its negative charge, Bacillus pasteuris itself acted as a nucleation site to attract strontium ions and the popcorn-like SrCO 3 crystals are formed under the secretion of microorganisms during the dissolution and recrystallization [24].…”
Section: Resultsmentioning
confidence: 99%
“…2G-I, Supplementary Figure 3C, Movies 1-3). Additionally, we examined the bacterial community diversity in the primary polyps by 16S rRNA and high-throughput sequencing, finding no evidence of calcium carbonate mineralizing bacteria [3538] at the genus level (Supplementary Figure 4 and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro precipitation experiments of Mg-calcite (with Ca/Mg molar ratio of four or greater) have shown that the forming crystal displays dumbbell shapes [3234]. Moreover, as similar mineral structures are induced by some bacteria [3538] the relationship between dumbbell formation and coral skeletal formation was suggested to result from biologically-induced, carbonate formation processes occurring in the leaky sea-water environment between the organism tissue and the substrate [27].…”
Section: Introductionmentioning
confidence: 99%
“…These factors directly affect the hydration reaction, pore structure, permeability, and compactness of the CUTB and thus affect its mechanical properties and leaching resistance. Numerous studies conducted by experts and scholars have shown that the complex physics and chemistry of uranium tailings affect the performance of cemented backfill, which restricts its use as aggregate in filling engineering applications [8][9][10][11][12]. Recently, many experts and scholars have paid a great deal of attention to smelting slag as a substitute for backfill cementitious materials.…”
Section: Introductionmentioning
confidence: 99%